Manipulating plasmon-exciton interactions in the plasmonic waveguide structure based on the dispersion relations concept - Mirahmadi, M.; Mahinroosta, T.; Hamidi, S. M. (Optical and quantum electronics, 2020)
We have introduced a new two-dimensional plexcitonic waveguide structure based on two dimensional plasmonic crystal covered by rhodamine B (RhB) and poly-vinyl-pirolydone (PVP) layer. The study ability to focus and confine optical energy in subwavelength regions at the nanoscale have been subjects of research recently. For this purpose, we fabricate gold nano structure by nano imprint lithography and cover it by RhB dye and PVP layer. To investigate propagation constant and thus light confinement in Gold/ RhB region, we use dispersion relation concept, by the aid of kramers–kronig relation in theoretical end experimental way, which confirms that we have enhance in light matter interaction in plexcitonic structure which is very useful for many applications such as plexcitonic switches.